Anglo-Saxon culture and the modern imagination - Clark, David, 1977-; Perkins, Nicholas (Woodbridge, Suffolk [England] ; Rochester, N.Y. : D.S. Brewer, 2010)
An excellent collection... breaks new ground in many areas. Should make a substantial impact on the discussion of the contemporary influence of Anglo-Saxon Culture. Conor McCarthy, author of Seamus Heaney and the Medieval Imagination Britain's pre-Conquest past and its culture continues to fascinate modern writers and artists. From Henry Sweet's Anglo-Saxon Reader to Seamus Heaney's Beowulf, and from high modernism to the musclebound heroes of comic book and Hollywood, Anglo-Saxon England has been a powerful and often unexpected source of inspiration, antagonism, and reflection. The essays here engage with the ways in which the Anglo-Saxons and their literature have been received, confronted, and re-envisioned in the modern imagination. They offer fresh insights on established figures, such as W.H. Auden, J.R.R. Tolkien, and David Jones, and on contemporary writers such as Geoffrey Hill, Peter Reading, P.D. James, and Heaney. They explore the interaction between text, image and landscape in medieval and modern books, the recasting of mythic figures such as Wayland Smith, and the metamorphosis of Beowulf into Grendel - as a novel and as grand opera. The early medieval emerges not simply as a site of nostalgia or anxiety in modern revisions, but instead provides a vital arena for creativity, pleasure, and artistic experiment. Contributors: Bernard O'Donoghue, Chris Jones, Mark Atherton, Maria Artamonova, Anna Johnson, Clare A. Lees, Sian Echard, Catherine A.M. Clarke, Maria Sachiko Cecire, Allen J. Frantzen, John Halbrooks, Hannah J. Crawforth, Joshua Davies, Rebecca Anne Barr.
7 BOOM : Seeing Beowulf in Pictures and Print8 Window in the Wall : Looking for Grand Opera in John Gardner's Grendel; 9 Re-placing Masculinity : The DC Comics Beowulf Series and its Context, 1975-6; 10 P.D. James Reads Beowulf; 11 Ban Welondes : Wayland Smith in Popular Culture; 12 'Overlord of the M5' : The Superlative Structure of Sovereignty in Geoffrey Hill's Mercian Hymns; 13 The Absent Anglo-Saxon Past in Ted Hughes's Elmet; 14 Resurrecting Saxon Things : Peter Reading, 'species decline', and Old English Poetry; INDEX; Backcover
Includes bibliographical references and index.
JSTOR
Keywords: Civilization, Anglo-Saxon.; Civilization, Anglo-Saxon, in literature; English literature -- Old English, ca. 450-1100 -- History and criticism; Civilisation anglo-saxonne.; Civilisation anglo-saxonne dans la littérature.; Littérature anglaise -- ca 450-1100 (Vieil anglais) -- Histoire et critique; HISTORY -- Europe -- Great Britain; LITERARY CRITICISM -- Medieval; Civilization, Anglo-Saxon; Civilization, Anglo-Saxon, in literature; English literature -- Old English; Altenglisch; Literatur; Angelsachsen; Kultur; Rezeption; Großbritannien; Bellettrie (teksten); Cultuurgeschiedenis (wetenschap); Engeland; 450-1100; Anglo-Saxons.; Artists; Beowulf; Comic book; Culture; Henry Sweet; Hollywood; Imagination; Inspiration; Literature; Medieval England; Modern writers; Pre-Conquest past; Criticism, interpretation, etc